Wetland square, market Pier: Designing for heritage in the New Zealand regional landscape - Murray, Rachel Sari-Dewi; Kebbell, Sam; Bryant, Martin (Interstices: Journal of Architecture and Related Arts, 2016)
Supervisors: Sam Kebbell, Martin Bryant This design-led research project addresses the rapid environmental degradation and socioeconomic decline to which many of New Zealand’s low-lying swampland regions have succumbed. The research critiques existing settlement patterns, investigating innovative urban forms that work dually to reactivate the wetland environments while increasing population density to levels required for public systems to function sustainably and vitally. The design project identifies a squared-off urban conservation wetland, transforming it into a new Wetland Square: a civic heart of the region’s natural and cultural heritage. A Market Pier is also proposed, extending from the urban edge of the town square towards the central wetland lagoon. The research rethinks traditional land conservation practice in New Zealand’s settled regional landscapes, stressing architecture’s responsibility to reconcile urban, ecological and cultural heritage systems to ensure environmental and community resilience in the regional landscape.